TOPIC: HEART FAILURE: MODERN DIAGNOSIS AND TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores heart failure as one of the pressing issues in modern medicine, analyzing its etiology, pathogenesis, and clinical course. The main factors contributing to the development of heart failure—ischemic heart disease, arterial hypertension, myocarditis, and cardiomyopathies—are separately examined. The role of modern diagnostic methods such as electrocardiography (ECG), echocardiography (ECHO), magnetic resonance imaging (MRI), and laboratory biomarkers in the early detection of heart failure is highlighted. In the treatment section, the effectiveness of pharmacological agents such as ACE inhibitors, beta-blockers, diuretics, as well as modern cardioimplantation techniques (pacemakers, defibrillators), is discussed. The study emphasizes that early diagnosis and a comprehensive treatment approach to heart failure are crucial for improving patients’ life expectancy and quality of life.